Human Relations in the Novel Hari Mulai Terang by Arafat Nur - Siti Rukiyah; Nova Dwi Mulyani; Feri Ariyanto; Sri Utami; Imayah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Literary texts are artistic products that write down the activities, behavior and social attitudes of society. Because of this, literature is seen as a photocopy of the reality of life. The aim of this research is to describe human relations in the literary novel Hari Mulai Terang by Arafat Nur. Human relations are human relations with social life including nature, God and oneself. Descriptive qualitative methods were used in this research with listening, reading and note-taking techniques. The analysis uses data content analysis which shows human relations. The results of the findings and analysis include: (a) human relations with themselves; (b) human relations with fellow humans; (c) human relations with nature; and (iv) human relationship with God. These findings encourage the existence of a social circle of figures who live in the local environment.